Website-Based Village Information System Design (Case Study: Ujung Batu III Village) - M. Rhifky Wayahdi; Surya Guntur (Jurnal Minfo Polgan, 2025)
This research aims to design a website-based village information system in Ujung Batu III Village, Hutaraja Tinggi, Padang Lawas, North Sumatra. With the rapid development of digital technology, websites have become an important tool for increasing information access, transparency and public participation. The research method used is the waterfall model, which includes the stages of communication, planning, modeling, construction and implementation. The research results show that the village information website has succeeded in increasing community access to important information, such as village activities and government programs. In addition, training provided to village officials and community representatives improves their skills in managing content sites, thereby encouraging community empowerment. This website also functions as a promotional tool to introduce the village's potential, including tourist attractions and local products, which can attract the attention of tourists and investors. Increased communication between the village government and the community via the website creates a more open and responsive channel. With a structured system, village information management can continue in a sustainable manner, ensuring the relevance and benefits of information for future generations. This research supports the development vision of Ujung Batu III Village and contributes to the welfare of the village community.